Cohort study of risk of fracture before and after surgery for primary hyperparathyroidism. Issue 7261 (9th September 2000) - Vestergaard, Peter; Mollerup, Charlotte L; Frøkjær, Vibe Gedsø; Christiansen, Peer; Blichert-Toft, Mogens; Mosekilde, Leif
Abstract: Objectives: To study whether fracture risk before and after surgery was increased in patients with primary hyperparathyroidism. Design: Cohort study. Setting: Three Danish university hospitals. Participants: 674 consecutive patients with primary hyperparathyroidism (median age 61, range 13–89 years) operated on during the period 1 January 1979 to 31 December 1997; 2021 age and sex matched controls from national patient register. Main outcome measure: Fractures. Results: The cases had an increased relative rate of fractures compared with the controls before surgery (1.8, 95% confidence interval 1.3 to 2.3) but not after surgery (1.0, 0.8 to 1.3). The risk of fracture was increased for the vertebrae (3.5, 1.3 to 9.7), the distal part of the lower leg and ankles (2.3, 1.2 to 4.3), and the non-distal part of the forearm (4.0, 1.5 to 10.6) before surgery but not after. The increase in risk of fracture began about 10 years before surgery. Risk peaked 5–6 years before surgery and remained raised, although at a lower level, in the five years immediately before surgery. A small increase in risk of fracture of the distal forearm emerged more than 10 years after surgery (2.9, 1.3 to 6.7). Conclusions: Risk of fracture is increased up to 10 years before surgery in patients with primary hyperparathyroidism. The risk returns to normal after surgery.